KAJIAN BERBAGAI TIPE PENGELOLAAN WILAYAH SUNGAI DI ASIA SEBAGAI ACUAN DALAM PENENTUAN SISTEM PENGELOLAAN SUMBER DAYA AIR - SURYA DEWI, NI MADE NIA BUNGA (GANEC SWARA, 2019)
The  Integrated Water Resources Management (IWRM)  is  significant  to do  in order  to obtain water  supply availability including inter-sector perspective, diverse of  water future needs, and  its present availability and  orientation  towards  the  'triple bottom  line',  such as  social, economi,c and environment.  In  the past decade,  most  countries  in Asia  have  already  adopted  national water  policies  that  advocate  IWRM  in  river  basins.  However, IWRM implementation is still at an early stage. IWRM at the basin level is best provided by a River Basin Organization (RBO)  by facilitating  and/ or implementing  various  development  processes   and  management.  Across Asia, a variety of small and large RBOs are now helping governments and stakeholders to implement IWRM in river basins.  Some RBOs operate within the structures of regular government departments. In  other  cases,  however,  a  corporate  or  quasi-corporate model  has  been  selected,  to  provide  RBOs  with  greater  autonomy  in  their  management,  capacity  development,  and  revenue  generation.  The research attempts to  study distinction between  three  types of RBO: council/committee, public/ government,  and  corporation. Thus, it can determine  the most  appropriate  type  of  river management  applied  in  river  basin